Maison de terre et de roseau : regards sur la bourrine du marais de Monts - François Le Bœuf (In Situ)
The rural buildings of the Monts marshes, a coastal zone to the north-west of the Vendée region, comprise a small group of « bourrines », modest peasants’ dwellings with walls of cobwork - earth and straw mortar - and roofs thatched in reeds. Some of the architectural dispositions of these buildings, as well as the construction techniques, are surprisingly archaic. Although these dwellings were built relatively recently, during the 19th century or the early years of the 20th, the « bourrine » might possibly a source of information on the « primitive house » dear to the ethnologist Jean Cuisenier.